Issues in language planning and language education: A survey from Macao on its return to Chinese sovereignty - Mann, Charles C. (Animo Repository, 1999)
This paper presents an overview of current language policy and planning in Macao, as well as the language situation, especially in relation to language in education. The situation of the four principal types of (language-medium) schools is also reviewed, with a view to assessing how efficiently they might be said to be achieving their proclaimed goals, and what problems they may be facing, with the approach of the return to Chinese rule. It also highlights and discusses the findings of a questionnaire- and interview-based mini-survey on language use, language preference, and language attitudes undertaken on a sample population of secondary-level pupils and teachers, university students and lecturers, and education administrators in the territory. Finally, some recommendations and prognoses are made, based on the trends of these findings, on the way forward in dealing with some of the problems this potentially conflictual situation (and the transitional phase of it) may create.